Legal and (or) welfare state: monism or pluralism? - S. V. Biryukov; A. E. Evstratov (Правоприменение, 2024)
The subject. Russian legal literature presents opposing approaches to the issue of the relationship between the legal and social states. The article examines the problems of scientific validity, social conditionality and compatibility of ideas about the legal and social state.The purpose. Classical ideas about the ideal social structure, characteristic of different directions of political and legal thought (rule of law; renunciation of the state (minimal state); unified system of public self-government (socialist state); social state) are aimed to be assessed in terms of a combination of socio-legal monism and pluralism, touches on the ideas of the special concept of legal pluralism.Methodology. A combination of the dialectical method with other methods is used: formal logic, modeling, formal legal and comparative legal, as well as theoretical-sociological and theoretical-cultural analysis.Main results and conclusions. It is possible to consider the model of a social legal state as an ideal way to resolve social contradictions, taking into account the following proposed clarifications to this model: (a) the idea of a welfare state, despite its various interpretations, primarily refers to the solution of socio-economic problems, while a balance of private and public interests is also necessary for intangible issues that cannot be resolved only through the acquisition of property; (b) complete harmony of private and public interests is an unattainable ideal, therefore, in a social legal state new contradictions will continue to arise between the private and public principles, the solution of which can be achieved if the following condition is met: “awareness of every interest of public interest in those areas of life where it necessary, and the development of a compromise of private interests where possible”; (c) the dialectical approach assumes that the model of a social legal state, as its goals are achieved, sooner or later must be revised (added).